Diseño de un programa preuniversitario que atienda las necesidades de los aspirantes con indecisión vocacional de la Universidad de la Costa (2024)
This project proposes the design of a pre-college program to serve vocationally undecided applicants at Universidad de la Costa. The main objective is to help students experience academic and occupational aspects of the programs of interest, thus facilitating the transition to university life and reducing career choice insecurity. Through dynamic and creative strategies, the pre-university program includes practical experiences that bring applicants closer to the reality of higher education, offering personalized guidance and fostering the comprehensive development of academic and personal competencies. The project uses tools such as surveys and empathy maps to better understand the needs of students and their families, proposing an innovative approach that combines academic and work experiences, supported by information and communication technologies. It also integrates a strategic map that establishes alliances with institutions and uses specific resources to guarantee the program's effectiveness. This approach seeks to reduce levels of vocational indecision, improve career guidance, and facilitate access to higher education for students in the region.